2009
DOI: 10.4137/oed.s2813
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of Antigen-presenting Cells within the Normal Cornea

Abstract: Abstract:The composition and location of professional antigen presenting cells (APC) varies in different mucosal surfaces. The cornea, long considered an immune-privileged tissue devoid of APCs, is now known to host a heterogeneous network of bone marrowderived cells. Here, we utilized transgenic mice that express enhanced green fluorescent protein (EGFP) from the CD11c promoter (pCD11c) in conjunction with immunohistochemical staining to demonstrate an interesting stratification of APCs within non-inflamed mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 25 publications
(80 reference statements)
4
51
0
1
Order By: Relevance
“…Bone marrow derived cells are present in the normal cornea (24,25), and we showed that TLR4 expression on resident bone marrow-derived cells can mediate the host response to LPS and P. aeruginosa (17,19); however, results from the current study demonstrate that MD-2 expression on either bone marrow-derived or on non-myeloid cells is sufficient to mediate an inflammatory response, indicating that in addition to bone marrow cells, there is also a role for corneal epithelial cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow derived cells are present in the normal cornea (24,25), and we showed that TLR4 expression on resident bone marrow-derived cells can mediate the host response to LPS and P. aeruginosa (17,19); however, results from the current study demonstrate that MD-2 expression on either bone marrow-derived or on non-myeloid cells is sufficient to mediate an inflammatory response, indicating that in addition to bone marrow cells, there is also a role for corneal epithelial cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…10 This difference in rejection rate can be explained, at least in part, by differential immunological responses between BALB/c and host C57BL/6 mouse strains. 11 MPS and other innate immune cells (some expressing MHCclass II antigens) are present in the corneal epithelial layer and stroma, [12][13][14][15][16] especially in the peripheral cornea (limbus). 17 Following the induction of inflammation, MPS are activated and the expression of MHC-class II, as well as co-stimulatory molecules, such as CD80 (B7.1), CD86 (B7.2), and CD40, is increased.…”
mentioning
confidence: 99%
“…24 -26 DCs are another cell population located at the basal layer of the corneal epithelium. 12,[27][28][29][30] Unlike PMNs and ␥␦T cells, which are usually not found in the cornea, 25,31 DCs are present and embedded in the epithelia of many mucosal surfaces. 1,5 Thus, both epithelial cells and intraepithelial DCs are in the front line facing external environments and can sense danger signals, including tissue injury and infection.…”
mentioning
confidence: 99%